(untitled) (European Journal of Marketing and Economics, 2019)
This study tries to understand the relationship among financial performance, environmental predictability and having strategy in the third (NGO) sector. The independent variable of the study is financial performance which is conceptualized as achieving the financial objectives which have been previously established. Environmental predictability is a sub-dimension of organizational environment that explains stability of the environment. Having strategy on the other hand is related with having mission and vision statements that are explicitly and clearly defined. The results of regression analysis indicate that, environmental predictability and having a clearly defined strategy have positive effects on financial performance in Non-Governmental Organizations.